2004
DOI: 10.1002/app.20126
|View full text |Cite
|
Sign up to set email alerts
|

Morphology and micromechanical deformation behavior of styrene–butadiene block copolymers. IV. Structure–property correlation in binary block copolymer blends

Abstract: ABSTRACT:The structure-property correlation in blends consisting of styrene/butadiene block copolymers forming alternating polystyrene (PS) and polybutadiene (PB) lamellae, and PS domains in rubbery matrix was investigated by different microscopic techniques (transmission electron microscopy, scanning force microscopy, and scanning electron microscopy), uniaxial tensile testing, and dynamic mechanical analysis. Unlike the pure lamellar block copolymer, the blends showed predominantly disordered wormlike morpho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…Although for partially miscible SB star block/triblock copolymer blends two brittle‐to‐tough transitions have been observed, the mechanical properties, such as σ y and the strain at break, depend exponentially or linearly on the composition 12, 13. The morphologies in this system resemble the neat copolymers, causing a simple change in the mechanical properties 17. In contrast, for the miscible LN3/LN4 system, consisting of blends of similar architectures, hexagonal and bicontinuous morphologies were observed that were not found in the neat copolymers, and they resulted in a nonmonotonic dependence of the mechanical properties on the composition.…”
Section: Resultsmentioning
confidence: 94%
“…Although for partially miscible SB star block/triblock copolymer blends two brittle‐to‐tough transitions have been observed, the mechanical properties, such as σ y and the strain at break, depend exponentially or linearly on the composition 12, 13. The morphologies in this system resemble the neat copolymers, causing a simple change in the mechanical properties 17. In contrast, for the miscible LN3/LN4 system, consisting of blends of similar architectures, hexagonal and bicontinuous morphologies were observed that were not found in the neat copolymers, and they resulted in a nonmonotonic dependence of the mechanical properties on the composition.…”
Section: Resultsmentioning
confidence: 94%
“…[7] In the last few decades, the structure-property relationships and the deformation mechanisms of di-and tri-block copolymers based on thermoplastic elastomers (TPE) containing glassy and rubbery segments have been investigated. [3,[8][9][10][11][12][13][14] In general, TPEs are composed of two or more microphase-separated components. The most commonly used TPE is the binary triblock copolymer polystyrene-b-polybutadiene-bpolystyrene, SBS.…”
Section: Introductionmentioning
confidence: 99%
“…Triblock copolymers with glass‐rubber‐glass chain architectures are observed to have high tensile strength when compared to diblock copolymers, which is due to the immobilisation of the elastomer segments in‐between nonelastomeric segments 8. Studies on the morphological and mechanical behaviour of different polystyrene/polybutadiene (PS/PB) triblock and starblock copolymer systems has given deeper insight into the characteristics of various molecular architectures 9–11. Phase behaviour and morphology of a symmetric and an asymmetric S‐(S/B)‐S triblock copolymer have been discussed by Lach et al,12 where the compositions of the S/B middle block and the PS outer blocks were found to have a significant influence on the miscibility and thus on the morphology of these copolymers.…”
Section: Introductionmentioning
confidence: 99%